Promyelocytic Leukemia Antigen Expression: a Histological Marker for Primary Biliary Cholangitis Diagnosis? - Papamichalis, Panagiotis A. (J Transl Int Med, 2021)
BACKGROUND AND OBJECTIVES: Distinguishing primary biliary cholangitis (PBC) from other cholestatic diseases at the histological level could be assisted by new methods, such as immunohistochemical staining of specific antigens. METHODS: We evaluated whether the detection of promyelocytic leukemia protein (PML) can serve as a specific and sensitive marker for PBC diagnosis. Liver biopsies from 26 PBC patients, 20 primary sclerosing cholangitis (PSC), 37 viral hepatitis, 11 non-alcoholic steatohepatitis (NASH) and 5 normal patients were investigated after immunostaining with the anti-PML monoclonal PG-M3, IgG1 antibody. RESULTS: Immunoreactivity in bile ducts was expressed by the PML-score (quotient of positive ducts to the total number of portal tracts multiplied by 2). PML-score was higher in PBC as compared to controls (P < 0.001). Using a cutoff of 0.18, PML-score proved highly sensitive (84.6%) and specific (89.7%) for confirming PBC as compared to only 5% of PSC, 9.1% of NASH and 13.5% of viral hepatitis patients (P < 0.001). Irrespective of the underlying disease, patients with PML-score > 0.18 were older (P = 0.007), more often females (P < 0.001) with higher ALP (P < 0.001), γ-GT (P = 0.001) and IgM (P < 0.001) compared to the patients with PML-score < 0.18. CONCLUSIONS: We postulate that a simple PML immunohistochemical test could be sufficient for histopathological discrimination of PBC in problematic cases of undefined cholestatic disorders, including small-duct PSC and AMA-negative PBC cases.